Identification of Hydrothermal Rock Alterations Based on Petrographic Analysis in Banturung Area, Bukit Batu District, Palangka Raya City - I Putu Putrawiyanta; Novalisae Novalisae; Noveriady Noveriady; Neny Fidayanti; Irga Loti Rante; Hendrik Brianto (Universitas Islam Raden Rahmat, Malang, 2025)
The Banturung region mostly consists of the morphology of igneous rock hills where most of the rocks physically show that they have undergone a process of change, so more detailed research is needed to distinguish the types of rocks that exist at the research site. This study aims to determine the distribution and types of rocks that undergo alterations at the research site. The research method with petrographic analysis, due to mineral changes and changes in rock composition in alterations can be observed from microscopic observations by paying attention to the mineral composition. The rock sample is cut into thin incisions measuring 0.035 mm so that it can be observed under a microscope. From the results of the rock incision analysis, it is known that the characteristics of rock alteration at the study site include the type of Phyllic alteration with serisite as a key mineral, with a very low alteration intensity < 25%, and hydrothermal alteration processes in dacite and tonalite rocks. This alteration process can be an early indication of the formation of metallic minerals or mineralization of valuable minerals at the research site, which is also strengthened by the discovery of pyrite minerals at the research site so that it can be further developed as a source of mineral resource research.